YIELD AND FRUIT QUALITY OF TOMATO CULTIVARS FERTIGATED WITH POTASSIUM CHLORATE AND POTASSIUM SULPHATE (Revista de Ciências Agroveterinárias, 2005)
The objective of this work was to evaluate the yield and fruit quality of tomato fertigated with potassium chlorate and potassium sulphate by a drip system irrigation. The experiment was carried out in a plastic greenhouse at the Campinas Experimental Station, IAC, Campinas, São Paulo, Brazil, from September 2000 to January 2001. The tomato cultivars used were Sweet Million, Rocio and Densus that were cultivated on slabs with agricultural substratum. The yield and the quality of tomato fruits were evaluated. The fruit quality was evaluated by the determination of total soluble solids content (TSS), total tritable acidity (TTA), pH, dry matter (DM) and the TSS/TTA ratio. The different sources of potassium affected tomato yield only for the genotype Densus. The pH of tomato juice was also influenced by potassium sources. The TSS, TTA, DM, and TSS/TTA values were only affected by the genotype.
Keywords: Lycopersicon esculentum Mill.; nutrient solution; pos-harvest; protected cultivation.